2013
DOI: 10.1021/je4001558
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Uncertainty of Ideal-Gas Entropy and Heat Capacity Calculations by Density Functional Theory (DFT) for Molecules Containing Symmetrical Internal Rotors

Abstract: The uncertainty of thermophysical data is indispensable information when reporting both experimental and calculated values. In this paper, we present an evaluation of the uncertainty of the ideal-gas entropy and heat capacity calculations by density functional theory (DFT) for molecules containing symmetrical internal rotors. The rigid-rotor harmonic oscillator (RRHO) and one-dimensional hindered rotor (1-DHR) models are compared as well as the effect of the scale factors employed. The calculations of the stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 63 publications
0
45
0
Order By: Relevance
“…[14][15][16] Density functional theory with different functionals and basis sets has been frequently employed in these calculations. 17,18 Other methods based on semi-empirical orbital theory 15,19 and molecular dynamics simulations [20][21][22] have also been used to estimate entropies. Many of these methods however, require considerable time and computational resources, and are therefore not suitable for applications where millions or billions of such calculations are required, such as in virtual screening for drug discovery.…”
Section: Entropy In Dockingmentioning
confidence: 99%
“…[14][15][16] Density functional theory with different functionals and basis sets has been frequently employed in these calculations. 17,18 Other methods based on semi-empirical orbital theory 15,19 and molecular dynamics simulations [20][21][22] have also been used to estimate entropies. Many of these methods however, require considerable time and computational resources, and are therefore not suitable for applications where millions or billions of such calculations are required, such as in virtual screening for drug discovery.…”
Section: Entropy In Dockingmentioning
confidence: 99%
“…[16][17][18] These studies have frequently made use of different functionals and basis sets. 19,20 Other methods based on semi-empirical orbital theory 17,21 and molecular dynamics simulations [22][23][24] have also been used to estimate entropies. Many of these methods however, require considerable time and computational resources, and are therefore not suitable for applications where millions or billions of such calculations are required, such as in virtual screening for drug discovery.…”
Section: Entropy In Dockingmentioning
confidence: 99%
“…A more limited approach was used byČervinka et al in analysing 5,6 the uncertainties resulting from using a one-dimensional hindered rotor (HR) model for a set of 60 closed shell molecules; they found that errors of 20% in the HR contribution to the entropy and of 5%…”
Section: Introductionmentioning
confidence: 99%